Assessing the Effectiveness of the National Human Rights Commission, India, vis-à-vis the Paris Principles Relating to the Status of National Human Rights Institutions - Kaundal, Ruchita; Shanthakumar, Sanjeevi (The Age of Human Rights Journal, 2023)
National Human Rights Institutions (NHRI) play an important role in monitoring and promoting international human rights norms in a country. However, in order to function as an effective NHRI, they must adhere to the “Paris Principles” of 1993. In 2023 the Indian NHRI prepares to renew its ’A’ grade accreditation. This offers an opportunity to assess the effectiveness of the institution in light of the aforementioned Principles. In doing so the authors address both the limitations that hinder the NHRI’s performance and the remedies. Notably, the role of “District Human Rights Courts”, in supporting the NHRI in enhancing its effectiveness.